Skin Manifestations in Rheumatic Disease - Matucci-Cerinic, Marco.; Matucci-Cerinic, Marco.; Furst, Daniel.; Furst, Daniel.; Fiorentino, David.; Fiorentino, David. (Springer New York : Imprint: Springer, 2014)
Rheumatologic diseases are highly associated with clinical symptoms of the skin, nails, and mucosal membranes. This book provides the practicing rheumatologist with a rapid, easy to consult reference to help interpret the nature of these cutaneous lesions and then quickly decide upon the appropriate follow-up tests. Utilizing an abundance of informative photographs, it contains all of the essential information needed for early diagnosis and treatment. This comprehensive guide properly orients the practitioner within the challenging world of rheumatologic disorders of the skin and gives insight into when consultation with a dermatologist is advisable.